2009
DOI: 10.2319/0003-3219(2009)079[0422:iarosm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Impaction and Retention of Second Molars: Diagnosis, Treatment and Outcome

Abstract: In more than half of the treated patients the second molars failed to erupt into a proper position. The most common treatment given (extraction of the second molar) was the least successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
1
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(104 citation statements)
references
References 0 publications
2
89
1
12
Order By: Relevance
“…These findings suggest that this intervention significantly increases the chance of impaction of mandibular second molars compared with the reported prevalence of impacted second molars in the general population, which ranged from 0.2% to 2.3%. [8][9][10][11][12] Although we considered several variables, including facial pattern, skeletal relationship, spacing, and presence of third molars, as possibly contributing to impaction of the mandibular second molar, only the pretreatment intermolar angle was found to be a significant predictor of impaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that this intervention significantly increases the chance of impaction of mandibular second molars compared with the reported prevalence of impacted second molars in the general population, which ranged from 0.2% to 2.3%. [8][9][10][11][12] Although we considered several variables, including facial pattern, skeletal relationship, spacing, and presence of third molars, as possibly contributing to impaction of the mandibular second molar, only the pretreatment intermolar angle was found to be a significant predictor of impaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although Brin et al 28 found no association between skeletal relationship and the eruptive position of the second molar, Behbehani et al 15 suggested that vertical condylar growth resulting in autorotation of the mandible contributes to a smaller gonial angle, leading to increased risk of third molar impaction. 28 Magnusson and Kjellberg 12 reported on a patient series in which 166 second molars were impacted. Seventy-eight teeth were associated with the presence of third molars, although it is not reported which arch was affected, or if there was any statistically significant relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…introdUcción La no erupción del segundo molar mandibular permanente es una condición relativamente baja, pero ha ido en aumento en los últimos años 1,2,3,4,5 . La Dra.…”
Section: Introductionunclassified
“…Variables como la distancia desde distal del primer molar al borde anterior de la rama mandibular, tamaño del ángulo formado entre el eje axial del segundo molar con el plano mandibular 2 . También se ha relacionado la no erupción del segundo molar con sexo, edad, presencia de terceros molares, pérdidas prematuras de dientes temporales, uso de aparatos para ganar espacio en el sector anterior 1,3,4,5 . La retención de segundos se relaciona también con tratamientos más largo, costosos y complejos 6,7,8,9 , por lo cual es de suma importancia enfocarse en el diagnóstico precoz 10 y tratamiento temprano.…”
Section: Introductionunclassified